Enhancing Vocational High School Students’ Reading Comprehension Through Critical Reading Tasks: An Action Research Study in Indonesia - Munir (Celebes Journal of Language Studies, 2025)
This study investigates the use of critical reading tasks to enhance the reading comprehension, engagement, and strategy use of Indonesian vocational high school students. A total of 36 eleventh-grade students at SMK Negeri 10 Makassar participated in two cycles of Classroom Action Research (CAR), incorporating tasks such as prediction, annotation, questioning, summarizing, and retelling. Data were collected through observations, student questionnaires, teacher interviews, and student work samples, and analyzed using both qualitative and quantitative methods. The findings revealed that critical reading tasks led to significant improvements in students' ability to identify main ideas, make inferences, and summarize texts. Additionally, students exhibited increased engagement and reduced reliance on dictionaries. The study highlights the value of structured reading tasks in promoting active reading and collaborative learning, while also identifying ongoing challenges related to vocabulary acquisition. The research provides practical insights for EFL teachers in vocational settings, demonstrating that critical reading strategies can foster higher-order thinking skills, enhance comprehension, and transform reading into an interactive, meaning-making process. The study concludes with recommendations for future research, including the exploration of vocabulary support and the application of critical reading tasks in other educational contexts.